2010
DOI: 10.1073/pnas.1003530107
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene activity duringArabidopsisseed development and identification of seed-specific transcription factors

Abstract: Most of the transcription factors (TFs) responsible for controlling seed development are not yet known. To identify TF genes expressed at specific stages of seed development, including those unique to seeds, we used Affymetrix GeneChips to profile Arabidopsis genes active in seeds from fertilization through maturation and at other times of the plant life cycle. Seed gene sets were compared with those expressed in prefertilization ovules, germinating seedlings, and leaves, roots, stems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
508
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(555 citation statements)
references
References 57 publications
40
508
1
6
Order By: Relevance
“…Our work also further demonstrates the utility of the Arabidopsis seed coat as a good model system for the identification of GTs involved in pectin, and particularly RG-I, biosynthesis. The usefulness of this model system has been enhanced recently by the establishment of global expression data sets covering seed coat development in Arabidopsis (Le et al, 2010;Dean et al, 2011). Although the exact role of AtGATL5 in the synthesis of RG-I remains to be determined, the work reported here provides impetus for future research using both polysaccharide structural approaches and biochemical studies of possible biosynthetic complexes to further elucidate the functions of AtGATL5 in RG-I synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work also further demonstrates the utility of the Arabidopsis seed coat as a good model system for the identification of GTs involved in pectin, and particularly RG-I, biosynthesis. The usefulness of this model system has been enhanced recently by the establishment of global expression data sets covering seed coat development in Arabidopsis (Le et al, 2010;Dean et al, 2011). Although the exact role of AtGATL5 in the synthesis of RG-I remains to be determined, the work reported here provides impetus for future research using both polysaccharide structural approaches and biochemical studies of possible biosynthetic complexes to further elucidate the functions of AtGATL5 in RG-I synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…S2A). In addition, data available from transcriptome analyses using RNA extracted from laser-capture-dissected seed coat tissue (Le et al, 2010; http://seedgenenetwork.net/arabidopsis) indicate that AtGATL5 transcript levels are low in the seed coat during early embryogenesis and that the levels rise from the linear cotyledon stage onward (Supplemental Fig. S2B).…”
Section: Atgatl5mentioning
confidence: 99%
“…S17), implicating a differential transcriptional regulation between embryo and endosperm. It was previously reported that TFs of MADS function in seed and endosperm development (Kang et al, 2008;Sreenivasulu et al, 2008;Bemer et al, 2010;Le et al, 2010;Agarwal et al, 2011;Hehenberger et al, 2012). AGL62, a MADS protein of Arabidopsis, is the direct target of FIS Polycomb group repressive complex2 (PRC2), establishing the molecular basis for FIS PRC2-mediated endosperm cellularization (Hehenberger et al, 2012).…”
Section: Differential Regulatory Mechanisms In Embryo and Endospermmentioning
confidence: 99%
“…Several TF family members are likely to play a role in cell fate determination, including C2C2-YABBY (GRMZM2G167824 and GRMZM2G529859) and GeBP (GRMZM2G036966) homologs, as well as in cell growth regulation and germination, including WRKY (Zhang et al, 2011a;GRMZM5G816457) and bHLH (GRMZM2G042920) homologs. On the other hand, the majority of TFs enriched in endosperm were families such as MADS, SBP, NAC, bZIP, Myb, and C2C2-GATA, most of which have been implicated in seed development (Sreenivasulu et al, 2008;Bemer et al, 2010;Le et al, 2010;Agarwal et al, 2011). A total of 33 TF genes were selected for confirmation of the differential expression between embryo and endosperm with real-time RT-PCR analysis.…”
Section: Survey Of the Gene Expression Regulators In Maize Seedmentioning
confidence: 99%
“…To test whether the nucellus undergoes HR-PCD, we analyzed seeds of the metacaspase1 (mc1) and lesions simulating disease1 (lsd1) mutants, which are affected in two major components of the HR-PCD machinery that positively and negatively regulate HR-PCD, respectively (Coll et al, 2010). Based on laser microdissection transcriptomics data, both MC1 and LSD1 are expressed in the chalazal area that includes chalaza and nucellus (Le et al, 2010). Nevertheless, mc1 and lsd1 mutant seeds displayed a wild-type nucellus phenotype (Supplemental Figure 3).…”
Section: The Nucellus Of Arabidopsis Seeds Partially Degenerates Aftementioning
confidence: 99%